2020
DOI: 10.1172/jci.insight.140940
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the gut microbiota in predicting response to cancer immunotherapy in metastatic melanoma

Abstract: BACKGROUND Identifying factors conferring responses to therapy in cancer is critical to select the best treatment for patients. For immune checkpoint inhibition (ICI) therapy, mounting evidence suggests that the gut microbiome can determine patient treatment outcomes. However, the extent to which gut microbial features are applicable across different patient cohorts has not been extensively explored. METHODS We performed a meta-analysis of 4 published shotgun metagenomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 41 publications
6
94
0
3
Order By: Relevance
“…Patients' responsiveness to ICI therapy was evaluated with RECIST 1.1 criteria where complete or partial responses are classified as responders and stable or progressive disease states as non-responders [19]. Since Peters et al's data did not have an explicit classification of responsiveness, patients with over 6 months of progression-free survival were regarded as responders and the others as non-responders as suggested by Limeta et al [11]. In total, 130 melanoma patients (66 responders and 64 non-responders) were used (Table 1).…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' responsiveness to ICI therapy was evaluated with RECIST 1.1 criteria where complete or partial responses are classified as responders and stable or progressive disease states as non-responders [19]. Since Peters et al's data did not have an explicit classification of responsiveness, patients with over 6 months of progression-free survival were regarded as responders and the others as non-responders as suggested by Limeta et al [11]. In total, 130 melanoma patients (66 responders and 64 non-responders) were used (Table 1).…”
Section: Datasetsmentioning
confidence: 99%
“…Many bacteria reported by those studies did not appear in multiple studies at the species level except Faecalibacterium prausnitzii and Bacteroides thetaiotaomicron. Also, previous attempt to train machine learning classifiers on microbiome profiles has shown relatively low accuracy in the prediction of ICI response on unseen data [11]. This suggests the need for curation of massive-scale studies to obtain statistical power to generalize microbial signatures to unseen data.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with Dublin et al, who demonstrated ICI-associated colitis in 29.4% of melanoma patients under anti-CTLA-4, and their gut microbiota was mainly composed of microorganisms belonging to the phylum of Bacteroidetes , families of Bacteroidaceae , Rikenellaceae and Barnesiellaceae [ 11 ]. A recently published meta-analysis of four shotgun metagenomic studies in metastatic melanoma patients receiving immunotherapy showed differences of microbial composition in the gut of responders and non-responders and examined the predictive value of this composition [ 64 ]. The gut of responders was enriched with unknown Ruminococcaceae and Faecalibacterium spp., Ruminococcus bicirculans and Barnesiella intestinihomini , whereas non-responders were mainly colonized by B. thetaiotaomicron , Adlercreutzia equolifaciens , Bifidobacterium dentium and unknown Mogibacterium spp.…”
Section: Gut Microbiota and Immunotherapymentioning
confidence: 99%
“…The gut of responders was enriched with unknown Ruminococcaceae and Faecalibacterium spp., Ruminococcus bicirculans and Barnesiella intestinihomini , whereas non-responders were mainly colonized by B. thetaiotaomicron , Adlercreutzia equolifaciens , Bifidobacterium dentium and unknown Mogibacterium spp. [ 64 ]. Moreover, comparison of gut microbial networks of responders and non-responders revealed that responders’ networks had an abundance of Mogibacterium , Anaerococcus and Eggerthella spp.…”
Section: Gut Microbiota and Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation